2018
DOI: 10.1080/2162402x.2018.1466770
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific MyD88 signaling is required for intestinal tumor initiation and progression to malignancy

Abstract: The signal adapter MyD88, an essential component of Toll-like receptor (TLR) signaling, is important for gut-microbiome interactions. However, its contribution to cancer and its cell-type specific functions are controversially discussed. Therefore, we generated new tissue-specific mouse models and analyzed the clinical importance in human colorectal cancer. A gene-trap was inserted into the murine Myd88 gene (Myd88LSL), yielding MyD88-deficient background with Cre-mediated re-expression in myeloid (MYEL) or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As MyD88 is widely expressed by different immune and nonimmune cells, emerging evidence has suggested that MyD88 plays different roles under different circumstances in different cells. Recently, it has been reported that MyD88 expression was crucial for progression to malignancy, with tumor-promoting functions both in intestinal epithelia and in myeloid cells (Holtorf et al, 2018). However, far less is known about the effects of MyD88 signaling-specific deficiency in myofibroblasts in a CAC mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…As MyD88 is widely expressed by different immune and nonimmune cells, emerging evidence has suggested that MyD88 plays different roles under different circumstances in different cells. Recently, it has been reported that MyD88 expression was crucial for progression to malignancy, with tumor-promoting functions both in intestinal epithelia and in myeloid cells (Holtorf et al, 2018). However, far less is known about the effects of MyD88 signaling-specific deficiency in myofibroblasts in a CAC mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54][55][56][57] Of note, unlike other TLRs, TLR3 signaling appears to require tyrosine phosphorylation upon dsRNA recognition, 58 and operates exclusively via an MYD88 innate immune signal transduction adaptor (MYD88)-independent mechanism. 59,60 Defective TLR3 activity contributes to numerous pathologies, including chronic inflammation, sepsis, autoimmune disorders and cancer. [61][62][63][64][65][66] Specifically, loss-of-function TLR3 polymorphisms have been associated with an increased risk for breast carcinoma, 67 cervical cancer, 68 oral squamous cell carcinoma, 69 hepatocellular carcinoma (HCC), 70 and colorectal carcinoma (CRC); 71 as well as with poor disease outcome in patients with CRC 72 and non-small cell lung carcinoma (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“… 52 57 Of note, unlike other TLRs, TLR3 signaling appears to require tyrosine phosphorylation upon dsRNA recognition, 58 and operates exclusively via an MYD88 innate immune signal transduction adaptor (MYD88)-independent mechanism. 59 , 60 …”
Section: Introductionmentioning
confidence: 99%
“…All Toll-like receptors (TLRs) except TLR3 activate NF-κB signaling through the MyD88 pathway [3]. MyD88/TLR signaling is overexpressed and associated with intestinal tumor formation and progression [4].…”
Section: Introductionmentioning
confidence: 99%